FURIN suppresses the progression of atherosclerosis by promoting macrophage autophagy. Issue 5 (24th April 2023) - Chen, Hongping; Zhang, Lihui; Mi, Shaohua; Wang, Hua; Wang, Chunxiao; Jia, Wenjuan; Gong, Lei; Dong, Haibin; Xu, Bowen; Jing, Yanyan; Ge, Peipei; Pei, Zhigang; et al.
Abstract: FURIN, a member of the mammalian proprotein convertases (PCs) family, can promote the proteolytic maturation of proproteins. It has been shown that FURIN plays an important role in the progression of atherosclerosis (AS). Current evidence indicates that autophagy widely participates in atherogenesis. This study aimed to explore whether FURIN could affect atherogenesis via autophagy. The effect of FURIN on autophagy was studied using aortic tissues from aortic dissection patients who had BENTALL surgery, as well as macrophages and ApoE−/− mice. In atherosclerotic plaques of aortic tissues from patients, FURIN expression and autophagy were elevated. In macrophages, FURIN‐shRNA and FURIN‐overexpression lentivirus were used to intervene in FURIN expression. The results showed that FURIN overexpression accelerated LC3 formation in macrophages during the autophagosome formation phase. Furthermore, FURIN‐induced autophagy resulted in lower lipid droplet concentrations in macrophages. The western blot revealed that FURIN regulated autophagy via the AMPK/mTOR/ULK1/PI3KIII signaling pathway. In vivo, FURIN overexpression resulted in increased macrophage LC3 formation in ApoE−/− mice atherosclerotic plaques, confirming that FURIN could inhibit the progression of AS by promoting macrophage autophagy. The present study demonstrated that FURIN suppressed the progression of AS by promoting macrophage autophagy via the AMPK/mTOR/ULK1/PI3KIII signaling pathway, which attenuated atherosclerotic lesion formation. Based on this data, current findings add to our understanding of the complexity of AS. Abstract : FURIN inhibits atherogenesis by inducing macrophage autophagy.